EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THREE STEPS INTERVIEW (TSI) DAN THINK PAIR SHARE (TPS) PADA MATERI FUNGSI DITINJAU DARI KECERDASAN LOGIS MATEMATIS SISWA KELAS VIII SMP NEGERI SE-KABUPATEN KLATEN TAHUN PELAJARAN 2015/2016 - Rahayu, Heni Septi; Budiyono, Budiyono; Usodo, Budi (Universitas Sebelas Maret, 2016)
Abstract: The purpose of this study was to determine the effect of the learning models TSI, TPS, and direct learning model on mathematics learning achievement viewed from the students logical mathematical intelligence. The type of this study was quasi experimental study with factorial design. The population were the eighth-grade students of junior high schools in Klaten Regency in the academic year of 2015/2016. Instruments used for data collection were mathematics achievement test and logical mathematical intelligence test. The data analysis technique used was the two-way ANAVA with unbalanced cell. Based on the hypothesis, it was concluded as follows. 1) The mathematics learning achievement of TSI was better than TPS and direct learning model, the mathematics learning achievement of TPS was better than direct learning model. 2) The mathematics learning achievement of the students with high logical mathematics was better than the students with average and low logical mathematics, the students with average logical mathematics was better than the students with low logical mathematics. 3) The students with high logical mathematics who were treated by TSI, TPS, direct learning models had the same mathematics learning achievement, students with low logical mathematics treated with TPS and TSI has the same result for both models and was better direct learning model, the students who were treated by TPS learning model was better than direct learning model, the students with low logical mathematics who were treated by TSI was same as TPS and was better than direct learning model. 4) In TSI learning model, the mathematics learning achievement of students with high logical mathematic was better than the students with both average and low logical mathematics, the students with average logical mathematic was better than students with low logical mathematics, in TPS learning model, the students with high logical mathematics was same as the achievement of students with average logical mathematics and was better than the students with low logical mathematic, in direct learning model, the students with high logical mathematics was better than the students with average and low logical mathematics, the students with average logical mathematics was same as the students with low logical mathematics.Keywords: Three Steps Interview, Think Pair Share Direct Learning Model, Logical Mathematical Intelligence.